The `light' and `medium' subunits of the photosynthetic reaction centre from Rhodopseudomonas viridis: isolation of the genes, nucleotide and amino acid sequence - Michel, H. (1986)
The `light' (L) and the `medium' (M) subunits of the photosynthetic reaction centre from Rhodopseudomonas viridis were isolated and their amino-terminal sequences, as well as the sequences of several chymotryptic peptides, determined. Rps. viridis DNA was cloned in the Escherichia coli plasmid pBR322. Mixed oligonucleotide probes derived from the amino acid sequences were synthesised and utilised to isolate one clone which contained the genes for the L and M subunits of the reaction centre as well as the α and β subunits of the light-harvesting complex and part of the gene for the reaction centre cytochrome. The nucleotide sequences of the L and M subunit genes and the derived amino acid sequences are presented. The L subunit consists of 273 amino acids and has a mol. wt of 30 571. The M subunit consists of 323 amino acids and has a mol. wt of 35 902. The primary structure is discussed in the light of the recently published secondary and tertiary structure which has shown that both subunits contain five membrane-spanning helices.